HUBUNGAN KEPEMIMPINAN DAN KETAHANMALANGAN DENGAN MOTIVASI - Kundriyah Kundriyah (Universitas Negeri Jakarta, 2012)
The objective of the research is to determine the relationship between Leadership and Adversity with Motivation . The research was conducted at public senior high school in East Jakarta, DKI Jakarta. The data was collected using survey research methods from 120 teachers as samples and selected by simple random sampling. The research are as follows: (1) there is positive correlation between Leadership with Motivation, (2) there is positive correlation between Adversity with Motivation, and (3) there is positive correlation between Leadership and Adversity collectively with Motivation. Therefore, Based on this result of research, it could be concluded that Motivation would increase if high Leadership and conducive Adversity is exist. Efforts to improve the leadership can be done through the implementation of the school principal leadership tasks in accordance with the main duties and functions. While efforts to increase adversity can be done through good self-management and positive attitude in all matters.